2017
DOI: 10.1093/ageing/afx020
|View full text |Cite
|
Sign up to set email alerts
|

Preventive oral health intervention among old home care clients

Abstract: the intervention had a positive effect on oral hygiene, however the number of teeth with plaque remained high, even after the intervention. Multiple approaches based on individual needs are required to improve the oral health of vulnerable older adults, including integrating dental preventive care into daily care plan carried out by home care nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 13 publications
2
51
0
4
Order By: Relevance
“…Registering a daily oral health treatment plan into the patient information system seems to improve daily oral health care during home visits. Nihtilä et al (2017) reported similar results [16]. When oral hygiene is registered into the daily treatment plan, the nurses make time for it.…”
Section: Discussionmentioning
confidence: 86%
“…Registering a daily oral health treatment plan into the patient information system seems to improve daily oral health care during home visits. Nihtilä et al (2017) reported similar results [16]. When oral hygiene is registered into the daily treatment plan, the nurses make time for it.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, adding oral hygiene protocols to the daily care routine has been shown to increase caregivers' motivation and willingness to support residents with their oral care, as well as improved oral health of senior residents 47,48. In previous study, we have also shown that a tailored oral health intervention can significantly reduce the number of plaque‐covered teeth and improve denture hygiene among older home care clients 49. Moreover, for older people living in regular day care centres and assisted living homes, adherence to daily oral hygiene routines helped them maintain their sense of autonomy and self‐worth 3.…”
Section: Discussionmentioning
confidence: 89%
“…2 Impaired cognitive function and dementia have been reported to be associated with various aspects of oral health state in both cross-sectional and longitudinal studies. [3][4][5][6][7][8][9][10][11] Maintaining oral health is an important integral component of general health, and previous studies have indicated it is a significant contributor to an individual's quality of life. 12 Pain, tooth loss and oral diseases (such as dental caries and periodontal disease) are common consequences of poor oral health.…”
Section: Introductionmentioning
confidence: 99%